Lifespan evaluation for a standard RV reducer based on fatigue strength theory - Gao, Song (Strojniški vestnik, 2024)
Rotate vector (RV) reducers are the two-stage deceleration device comprising involute and cycloid-pin gear transmission mechanisms. As the typical deceleration elements, they are widely applied in industrial robots, digitally controlled machine tools and automation fields due to their compact structure and high precision. However, a reducer may lose precision after a long-term operation. Moreover, pitting and metal peeling of internal components may also occur, leading to a fatigue failure. Therefore, it is necessary to conduct investigations on lifespan evaluation for RV reducers. In this study, the CRV-80E reducer is taken as the research object. Firstly, according to its transmission characteristics, the lifespan evaluation model for a standard RV reducer is established based on fatigue strength theory and Palmgren-Miner linear cumulative damage law, with the internal crankshaft bearing is considered as the key component. Then, the simulations are carried out on crankshaft bearing by the ANSYS Workbench and SKF SimPro. The contact stress, deformation on bearing rollers, and the rated lifespan of the reducer are simulated. Finally, the accelerated life test is conducted on an RV reducer by increasing the external load with the positioning precision as an output and criterion. After the test, the reducer is disassembled, and metal peeling failure is observed on the crankshaft bearing while other parts are relatively intact. The test results validate the feasibility and accuracy of the service life evaluation model and simulation analysis. This study provides a new research approach for researchers and manufacturers and a design reference for engineers to improve the lifespan of RV reducers by optimizing crankshaft bearings, which have a certain academic value.
Keywords: accelerated tests; crankshaft bearings; ležaji ročične gredi; lifespan evaluation; pospešeni testi; reduktorji tipa RV; RV reducers; simulacijska analiza; simulation analysis; teorija časovne dinamične trdnosti; vrednotenje življenjske dobe